Rancang Bangun Antena Mikrostrip Triangular Patch Planar Array 2x2 Elements Frekuensi 1,2 GHz untuk Penerima Video Wireless LCD Projector - Muhammad Nur Tri Yuliarto; Agus Wagyana (Politeknik Negeri Jakarta, 2021)
LCD projectors are widely used to support presentations on teaching and learning activities, meetings, seminars and so on. This study discusses the design and manufacture of a 2x2 planar array triangular patch microstrip antenna as a receiving antenna for wireless LCD projectors to overcome cable length limitations. The research method starts from the design, simulation of design results, fabrication, parameter measurement and antenna testing. The design was carried out using the CST Studio Suite application, then made on the FR-4 PCB. Testing includes measurement of antenna parameters and performance. In testing the antenna parameters, the values ​​obtained are in accordance with predetermined specifications, gain above 3 dB, VSWR below 2 dB, return loss below -10 dB and unidirectional radiation pattern. The antenna performance test results show that the quality of signal and video reception from the microstrip receiving antenna that has been made is still better than the default antenna for the receiver device. Keywords: Microstrip triangular patch plannar 2x2 elements, wireless LCD projector